Interleukin-22 regulates antimicrobial peptide expression and keratinocyte differentiation to control Staphylococcus aureus colonization of the nasal mucosa - MILLS, KINGSTON; MCLOUGHLIN, RACHEL (My University, 2016)
The local immune response occurring during Staphylococcus aureus nasal colonization remains ill-defined. Studies have highlighted the importance of T-cell immunity in controlling S. aureus colonization of the nasal mucosa. We extend these observations, identifying a critical role for interleukin (IL)-22 in this process. IL-22 is basally expressed within the nasal mucosa and is induced upon S. aureus colonization. IL-22 is produced by CD4+ and CD8+ T lymphocytes at this site, with innate-like lymphocytes also contributing. IL-22−/− mice demonstrate significantly elevated levels of S. aureus nasal colonization as compared with wild-type (WT) mice. This was associated with reduced expression of antimicrobial peptides (AMPs) in the nose. Furthermore, expression of staphylococcal ligands loricrin and cytokeratin 10 was higher in the noses of IL-22−/− as compared with WT mice. IL-17 has been shown to regulate S. aureus nasal colonization by controlling local neutrophil responses; however, IL-17 expression and neutrophil responses were comparable in the noses of IL-22−/− and WT mice during S. aureus colonization. We conclude that IL-22 has an important role in controlling S. aureus nasal colonization through distinct mechanisms, with IL-22 mediating its effect exclusively by inducing AMP expression and controlling availability of staphylococcal ligands.
PUBLISHED
Cited By :1 Export Date: 8 December 2016
Keywords: Staphylococcus aureus nasal colonization; Staphylococcus aureus nasal colonization; Immunology, Inflammation & Infection